Assessment of free-rotating air swirling device to reduce SI engine emissions and improve fuel economy - Kafafy, Raed Ismail; Che Mat, Sharzali (Inderscience Enterprises Ltd., 2011)
Claims are furnished in several patents that swirling the intake air in SI engines can improve fuel economy and reduce environmental impact. In this paper, we investigate the effect of a free rotating air swirling device (FRASD) installed in the air intake hose on the overall performance and emission characteristics of an SI engine. FRASDs with three vane angles were tested; 6, 9 and 12 degrees. The baseline engine was tested without FRASD at selected loads. Then, the engine was tested at the same loads with each FRASD and results were compared with the baseline engine. Experiments show that all tested FRASDs exhibit some degree of enhancement in the overall performance and reduction in exhaust emissions. It was found that enhancement greatly depends on the engine operating condition in addition to the FRASD vane angle. Specifically, best enhancement in performance and highest reduction in emissions was observed with the 9-degrees which reduced specific fuel consumption by 12%, hydrocarbon (HC) emissions by 20% and carbon monoxide emissions by 12%. Suggestions are made to modify the FRASD design to magnify its impact on engine performance.